2018
DOI: 10.1002/jcla.22415
|View full text |Cite
|
Sign up to set email alerts
|

What should be the laboratory approach against isolated prolongation of a activated partial thromboplastin time?

Abstract: Prolonged APTT results should always be retested using a different assay prior to mixing study. The clinician and the laboratory specialist should collaborate at the postanalytical phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…From the viewpoint of clinical medicine, two conflicting disease categories, such as hemorrhagic diseases and thrombotic diseases, should be considered. Hemorrhagic disease is AHA, and thrombotic disease is antiphospholipid syndrome with positive lupus anticoagulant [3]. AHA exhibits reduction of FVIII levels.…”
Section: Discussionmentioning
confidence: 99%
“…From the viewpoint of clinical medicine, two conflicting disease categories, such as hemorrhagic diseases and thrombotic diseases, should be considered. Hemorrhagic disease is AHA, and thrombotic disease is antiphospholipid syndrome with positive lupus anticoagulant [3]. AHA exhibits reduction of FVIII levels.…”
Section: Discussionmentioning
confidence: 99%
“…In preparation for this review, a PubMed search comprising the search terms (“postanalytical” OR “post‐analytical”) AND (“Willebrand” OR “haemophilia” OR “hemophilia”) only captured 4 documents, not all of which were relevant to haemophilia/VWD, and thus confirming a serious under‐recognition of the influence of postanalytical issues on VWD and haemophilia diagnosis/exclusion, or perhaps more correctly reflective of increased potential for “misdiagnosis” of VWD or haemophilia. Postanalytical considerations reflect events after the test has been performed.…”
Section: An Overview Of Preanalytical Analytical and Postanalytical mentioning
confidence: 99%
“…However, these studies were performed using frozen samples, and no sex stratification was applied. There have been concerns regarding the quality of the earlier studies on BV, and consequently, the reliability of the BV estimates reported in these studies as well as the online 2014 BV database…”
Section: Introductionmentioning
confidence: 99%
“…stratification was applied. There have been concerns regarding the quality of the earlier studies on BV, 1,2 and consequently, the reliability of the BV estimates reported in these studies as well as the online 2014 BV database. 3 In this study, we aimed to determine BV estimates for PT, aPTT, and fibrinogen tests by analyzing fresh plasma samples following 1 hour of sampling.…”
mentioning
confidence: 99%